Classic animal models of Parkinson's disease: a historical perspective. Issue 4 (June 2019) - Hamadjida, Adjia; Frouni, Imane; Kwan, Cynthia; Huot, Philippe
Abstract : The quest to better understand the pathophysiology of Parkinson's disease (PD) and to find new therapies to provide greater relief to affected patients continues. The use of animal models of PD has been invaluable in the process. Here, we review, through a historical lens, some of the contribution of the 6-hydroxydopamine-lesioned rat and of the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-lesioned nonhuman primate, in refining our understanding of PD and its treatment-related complications. We examine the mechanisms underlying the toxicity of 6-hydroxydopamine and 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine, and then explore some of the advances at the molecular, pharmacological, electrophysiological and surgical levels made while experimenting on these animal models. We also discuss behavioural testing that can be performed with these animal models and highlight some of their limitations.